Increased competency in preparing feasibility study documents for pasteurized milk processing business - Rostiana, Endang; Ratnamiasih, Ina; Ratifah, Ifa; Herdiansyah, Endra; Baihaqi, Muhammad Iqbal; Gumilar, Dedi (Jurnal Pembelajaran Pemberdayaan Masyarakat (JP2M), 2024)
This study aims to analyze the business feasibility of the pasteurized milk production reactivation program in the Milk Processing (MP) business unit.  Feasibility analysis is carried out based on technical and production aspects, market and marketing aspects, management and human resource aspects, and financial aspects. The research method uses business feasibility analysis methods with observation, interview, and literature study approaches. The data collected consists of primary data and secondary data. Primary data collected in the form of questionnaires given to consumers in expressing their opinions on marketing aspects.  Furthermore, the secondary data used includes financial statements, sales reports, and production reports of the MP business unit of PT Agronesia. The results showed that the plan to re-operate the MP-BMC business unit of PT. Agronesia with a planned production of three products, namely pasteurized milk, yogurt, and ice cream estimated in the next 10 years is feasible to run. This feasibility is viewed from the financial aspect by calculating investment criteria, namely Net Present Value (NPV), Interest Rate of Return (IRR), Net Benefit Cost Ratio (B/C Ratio), and Pay Back Period (PBP), which is supported by the feasibility of other business managerial aspects.